Food Systems, Environments, Nutrition: a Structured Evidence Framework (FoodSENSE Framework) Application in Masaka District, Central Uganda - Caulfield, Mark; Achandi, Esther; Hammond, James; Omosa, Esther; Ahumuza, Ronnie; Spray, Andrea; Dominguez-Salas, Paula; Ouma, Emily A. (International Livestock Research Institute, 2024)
There is an increasing recognition that achieving food security and good nutrition requires coordinated multisectoral action. The causes of malnutrition are multifaceted and often interlinked. To improve food security, a good understanding of the different dimensions in the food system and food environment is important to prioritize intervention points. The concept of the “food system” has become an organizing narrative in recent years, with UN agencies and national governments developing food systems action plans. There is however a gap at finer-grained spatial levels: there are few guidelines on how to implement food systems thinking at the more local levels, guiding local decision making.